Aktivitas Sediaan Gel dari Ekstrak Lidah Buaya (Aloe barbadensis Mill.) pada Proses Persembuhan Luka Mencit (Mus musculus albinus) - Vetnizah Juniantito; Bayu Febram Prasetyo (Jurnal Ilmu Pertanian Indonesia, 2006)
The purpose of this study was to examined the effectivity of Aloe vera gel formulation on the skin wound healing process based on the macroscopic and microscopic observation. Fourty five DDY strain, 6-8 weeks old mice were used for experimental animals. Mice were incised 1-1.5 cm in the dorsum using sterile scalpels. Mice were divided into three groups. Group I (control) were not treated by anything, Group II were treated by commercial drugs (Bioplacenton), and Group III were treated by Aloe vera gel. Bioplacenton and Aloe vera gel were given topically twice a day to the skin using sterile cotton buds. Each groups consisted of 15 mice and distributed into 5 observation days with 3 replication. Three mice from each groups were euthanized periodically at day 3rd, 5th, 7th, 14th, and 21st post incision for gross pathology examination and to sampling the skin. Gross examination revealed that Bioplacenton and Aloe vera gel showed better result on wound healing process, i.e. the scab formation, scab peeler and unite of the wounded skin edge compared to the control groups. Microscopically, the Bioplacenton and Aloe vera gel groups showed the fastest epidermal re-epithelization compared with the control group. Qualitatively Bioplacenton and Aloe vera gel groups showed more fibrosis and collagen fibres formation than the control groups especially at day 7th and 14th. Scoring Average of neocapillaries formation from all groups showed no difference. Scoring average of inflammatory cells number revealed that control groups showed more cells than the other groups that indicated an high inflammatory activity. Based on macroscopic and microscopic examination we suggest that the Aloe vera gel formulation has a benefit to promote wound healing, and could be used for the treatment of skin wound. Thus, the Aloe vera gel formulation is potential to developed as commercial drugs.